THE EXPERIENCE OF SOME COUNTRIES IN IMPROVING TOURIST ATTRACTIVENESS AND THE ROLE OF THE MEDIA IN THIS PROCESS (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
Globalization that embraced the whole world in all areas of life in the XXI century has become an integral feature for tourism. Tourism is a largely social category. And it formed on the basis of numerous Factors. The tourism industry moves huge masses of people around the world. Nevertheless, one must understand that a traveler chooses a certain country, a certain region, which has its own developed approach to organizing tourism activities. The experience of some countries in the development of tourism, in particular the Czech Republic and Hungary, can be of great help in the development of the tourism industry in Armenia. A special mission in this process is given to the media. Their goal is to convey to the potential tourist information provoking positive associations.
Keywords: globalization; tourism industry; media; sights; tourism attraction; established image; visiting card; positive associations; association fixing